2020
DOI: 10.1055/s-0040-1710384
|View full text |Cite
|
Sign up to set email alerts
|

Primary Total Knee Arthroplasty: Correlation between Preoperative Radiographic Severity of Arthritis and Postoperative Patient Satisfaction

Abstract: Predicting postoperative outcomes following total knee arthroplasty (TKA) is important for patient selection. This study focuses on patient-reported outcomes and satisfaction in relation to preoperative radiographic arthritis severity. A retrospective chart review of 420 TKAs was performed. Patient satisfaction was determined using a structured telephone survey with questions focused on degree of satisfaction whether they would have surgery again and their ability to kneel. The radiographic severity of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Other methods included a simple binary scale (satisfied: yes or no), willingness to undergo surgery again (yes or no), and use of a numeric or visual analogue scale (VAS). Our internal review of more recent literature found similar single-question methods used in many studies [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Validated Patient Satisfaction and Quality Of Life Scalesmentioning
confidence: 78%
See 3 more Smart Citations
“…Other methods included a simple binary scale (satisfied: yes or no), willingness to undergo surgery again (yes or no), and use of a numeric or visual analogue scale (VAS). Our internal review of more recent literature found similar single-question methods used in many studies [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Validated Patient Satisfaction and Quality Of Life Scalesmentioning
confidence: 78%
“…A multitude of studies have investigated the ability of various factors to predict or correlate with patient satisfaction after TKA [3,9,10,[27][28][29][30][31][32][33][34][35]. Walker et al [12] found that the WOMAC score 1 year postoperatively could be used to predict patient satisfaction in 2578 patients.…”
Section: Predictors Of Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this nding, preoperative joint width rather than exion contracture of knee seems to be appropriate to represent the severity of arthritis. In the study conducted by Katie Rooks, they found out that the severity of preoperative radiographic arthritis(K-L grading scale)was associated with a higher degree of satisfaction [20] . This conclusion was in accordance with our result as well.…”
Section: Discussionmentioning
confidence: 99%